Sejarah dan Peran Muhammadiyah untuk Kemajuan Indonesia - Aisyah Khoirunni’mah Al Mufarriju (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The presence of Muhammadiyah in Indonesian history has been an important part of the journey of social progress, education and social welfare. This article discusses the significant role of Muhammadiyah in encouraging Indonesia's development from time to time. This research uses a historical approach to analyze Muhammadiyah's role in fighting for independence, building educational infrastructure, and promoting the values ​​of social justice and prosperity. Key words such as